An integrated biorefinery approach based on spent coffee grounds valorization - Pérez-Merchán, Antonio Manuel; Moreno-Tost, Ramón; Malpartida-García, Irene; García-Sancho, Cristina; Mérida-Robles, Josefa María; Maireles-Torres, Pedro Jesús (Elsevier, 2025)
Spent coffee grounds (SCGs) are an abundant lignocellulosic biomass with significant potential for industrial valorization, with great social and environmental benefits, due to their rich composition in cellulose, hemicellulose and lignin. In this study, the organosolv process, a method widely used in the paper industry, was employed to efficiently fractionate SCGs into their primary components. Hemicellulosic liquors containing up to 25 wt% sugars, predominantly galactose and mannose, were successfully extracted and subsequently dehydrated to produce 5-hydroxymethylfurfural (5-HMF), reaching a maximum yield of 90 % within 15 min of reaction time. The residual cellulose and lignin fractions were characterized by X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR), confirming their effective separation. These findings highlight the viability of SCGs as a sustainable feedstock for biorefinery applications, contributing to waste valorization and the development of a circular economy.
Keywords: Café - Uso; Spent coffee grounds (SCGs); Organosolv; 5-Hidroxymethylfurfural; Biomass Valorization